The Reception and Dissemination of European Music Theories in Brazil. Riemann, Schenker, and Schoenberg - Carlos de Lemos Almada; Guilherme Sauerbronn de Barros; Rodolfo Coelho de Souza; Cristina Capparelli Gerling; Ilza Nogueira (Zeitschrift der Gesellschaft für Musiktheorie)
The history of music theory in Brazil is still not adequately represented in Brazilian musicology. When the Brazilian Association for Music Theory and Analysis (Associação Brasileira de Teoria e Análise Musical – TeMA) was founded in 2014, it took upon itself the task of redressing this imbalance by creating a study group dedicated to the “Historiography of Brazilian Music Theory and Analysis” (“Produção teórica e analítica no Brasil: trajetórias e identidades”). This article represents the group’s first step toward developing a historiographical and critical literature related to theoretical and analytical music studies in Brazil. It aims at historicizing the absorption and development of European theories in the country and at showing how the idiosyncratic use of European theories in Brazil has been informed by pedagogical and research practice. Mostly dedicated to Brazilian musical contexts, theoretical-analytical studies developed in Brazil have creatively deployed imported theoretical models for pedagogical, analytical, or compositional purposes. European theories, such as those of Hugo Riemann, Heinrich Schenker, and Arnold Schoenberg, have been subject to distinctive interpretations in Brazilian academic research. // Die brasilianische Musikwissenschaft ist bislang der Geschichte der Musiktheorie in Brasilien nicht gerecht geworden. Als die Brasilianische Gesellschaft für Musiktheorie und Musikanalyse (Associação Brasileira de Teoria e Análise Musical – TeMA) im Jahr 2014 gegründet wurde, nahm sie sich vor, diesem Defizit entgegenzuwirken und gründete die Studiengruppe “Historiographie der brasilianischen Musiktheorie und Analyse“ (“Produção teórica e analítica no Brasil: trajetórias e identidades”). Dieser Aufsatz stellt den ersten Schritt der Gruppe zur Entwicklung einer historiographischen und kritischen Literatur zu den musiktheoretischen und -analytischen Studien in Brasilien dar. Er zielt darauf ab, die Rezeption und Entwicklung von europäischen Theorien in Brasilien nachzuzeichnen und zeigt dabei, wie Pädagogik und Forschung einen eigenständigen Gebrauch dieser Theorien bestimmt haben. Die in Brasilien erarbeiteten theoretischen und analytischen Studien, die hauptsächlich brasilianischen musikalischen Kontexten gewidmet sind, haben in kreativer Weise eingeführte theoretische Modelle für pädagogische, analytische oder kompositorische Zwecke weiterentwickelt. Unter den Theorien europäischer Herkunft haben diejenigen von Hugo Riemann, Heinrich Schenker und Arnold Schönberg in der brasilianischen Forschung eine spezifische Prägung erhalten.